Association between handwashing practices and quality of toilets with diarrhea among under-five years children - Yesvi Zulfiana; Luh Seri Ani; Ni Wayan Arya Utami (Universitas Udayana, 2018)
Background and purpose: The incidence of diarrhea among underfive years children in Indonesia is considerably high. Studies exploring risk factors of diarrhea have been extensively conducted in Indonesia. However, the association between handwashing practices of the mother and quality of toilets with diarrhea among under-five years children are still inconsistent across studies. This study aims to examine the association between handwashing practices of the mother, quality of toilets and the episodes of diarrhea among under-five years children. Methods: A cross-sectional survey was conducted involving 104 under-five years children in Selagalas Village. Samples were selected using systematic random sampling. Data were collected in July 2017 by observation and face-to-face interviews using questionnaires. Bivariate analysis and logistic regression were conducted to examine the association between hand washing practices, quality of toilets and diarrhea among under-five years children. Results: We found more than half of under-five years children (64.42%) had experienced at least one episode of diarrhea over the last three months. We found a significant association between diarrhea with unhygienic toilets with an adjusted odds ratio (AOR) of 2.84 and poor handwashing practices of the mother with AOR of 2.46, however, both have a lower limit of AOR confidence interval that close to one, namely 95%CI: 1.05-5.97 and 95%CI: 1.03-5.87. Conclusion: Poor hand washing practices and unhygienic toilets are associated with the episodes of diarrhea among under-five years children, however, both have a low programmatic importance. Further study should be carried out to understand the association between handwashing practices and quality of toilets with diarrhea. Despite of the low programmatic importance, good hand washing practice should be promoted and access to toilets that meet the health standard must be enhanced.